Key predictors and burden of meticillin-resistant Staphylococcus aureus infection in comparison with meticillin-susceptible S. aureus infection in an Australian hospital setting. (November 2022) - Miyakis, S.; Brentnall, S.; Masso, M.; Reynolds, G.; Byrne, M.K.; Newton, P.; Crawford, S.; Fish, J.; Nicholas, B.; Hill, T.; van Oijen, A.M.
Summary: Background: Staphylococcus aureus is associated with significant mortality and increased burden on the healthcare system. Relatively few reliable estimates are available regarding the impact of meticillin-resistant S. aureus (MRSA) infection compared with meticillin-susceptible S. aureus (MSSA) infection. Aims: To compare patients with MRSA infection and MSSA infection to identify differences in inpatient mortality, length of stay and costs of hospital services, and identify predictors of MRSA as a cause of S. aureus infection. Methods: An analytical, retrospective, longitudinal study using non-identifiable linked data on adults admitted to hospitals of a health district in Australia with a diagnosis of S. aureus infection over a 10-year period. The main outcome measure was 30-day inpatient mortality. Secondary endpoints included total overnight stays, all-cause inpatient mortality, and hospitalization costs within 1 year of index admission. Findings: Inpatient mortality at 30, 100 and 365 days was estimated to be significantly greater for patients with MRSA infection. The mean additional cost of MRSA infection when controlling for additional factors was $5988 and 4 nights of additional hospital stay per patient within 1 year of index admission. Key predictors of MRSA infection were: date of index admission; higher comorbidity score; greater socio-economic disadvantage; admission to hospital other than via the emergency department; older age; and prior admission to hospital within 28 days of index admission. Conclusions: MRSA infection is associated with increased inpatient mortality, costs and hospital length of stay compared with MSSA infection. Efforts are required to alleviate the additional burden of MRSA infection on patients and healthcare systems.